2019
DOI: 10.1093/carcin/bgz153
|View full text |Cite
|
Sign up to set email alerts
|

Neural crest-derived tumor neuroblastoma and melanoma share 1p13.2 as susceptibility locus that shows a long-range interaction with the SLC16A1 gene

Abstract: Abstract Neuroblastoma (NB) and malignant cutaneous melanoma (CMM) are neural crest cells (NCC)-derived tumors and may have a shared genetic basis, but this has not been investigated systematically by genome-wide association studies (GWAS). We took a three-staged approach to conduct cross-disease meta-analysis of GWAS for NB and CMM (2101 NB cases and 4202 controls; 12 874 CMM cases and 23 203 controls) to identify shared loci. Findings were replicated in 1403 NB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 49 publications
(35 reference statements)
1
17
0
2
Order By: Relevance
“…Although the high values of rNSM would suggest a tumor suppressor role for SLC16A1 , several studies suggest that the protein may serve a pro-oncogenic role. For example, depletion of SLC16A1 was found to decrease cellular proliferation and invasion in both neuroblastoma and malignant cutaneous melanoma cell lines, suggesting its role as an oncogene (OG; Avitabile et al, 2020 ). The pro-oncogenic role of MCT1 is also supported by the results of studies on esophageal squamous cell carcinoma (ESCC).…”
Section: Examples Of Genes With Strong Signatures Of Positive And/or mentioning
confidence: 99%
“…Although the high values of rNSM would suggest a tumor suppressor role for SLC16A1 , several studies suggest that the protein may serve a pro-oncogenic role. For example, depletion of SLC16A1 was found to decrease cellular proliferation and invasion in both neuroblastoma and malignant cutaneous melanoma cell lines, suggesting its role as an oncogene (OG; Avitabile et al, 2020 ). The pro-oncogenic role of MCT1 is also supported by the results of studies on esophageal squamous cell carcinoma (ESCC).…”
Section: Examples Of Genes With Strong Signatures Of Positive And/or mentioning
confidence: 99%
“…Although the high values of rNSM would suggest a tumor suppressor role for SLC16A1, several studies suggest that the protein may serve a pro-oncogenic role. For example, depletion of SLC16A1 was found to decrease cellular proliferation and invasion in both neuroblastoma and malignant cutaneous melanoma cell lines, suggesting its role as an oncogene (Avitabile et al, 2019). The pro-oncogenic role of MCT1 is also supported by the results of studies on esophageal squamous cell carcinoma ESCC.…”
Section: Monocarboxylate Transporter 1 Mct1 Encoded By the Slc16a1 Genementioning
confidence: 84%
“…In addition, Avitabile et al. 18 identified that 1p13.2 was a common susceptibility locus for neuroblastoma and melanoma risk by examining pleiotropy across two neural crest cell-derived tumors. Testori et al.…”
Section: Introductionmentioning
confidence: 99%